PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA VII-A SMPN 3 SIKUR KECAMATAN SIKUR T.P. 2022/2023 - Zainuddin Zainuddin (JURNAL ASIMILASI PENDIDIKAN, 2023)
The purpose of this study was to determine the use of problem-based learning models on the results of learning mathematics in square shape material in Class VII-A SMPN 3 Sikur, Sikur District. This research is a classroom action research. Classroom action research is research conducted in the classroom to improve or strengthen the quality of learning in the classroom. The survey subjects were class VII-A students of SMPN 3 Sikur, totaling 38 students. The object of this study is the Prolem Based Learning model to improve student learning outcomes. The research data is the test scores of student learning outcomes using the Problem Based Learning model in the mathematics subject matter of Square Shapes. After the data is obtained and analyzed, it can be seen that the results of students' mathematics learning in Square material in class VII-A students of SMPN 3 Sikur, Sikur District before and after the action are as follows: (1). The repeat value of the first cycle after the action with an average of 68.81, and 60.53% classical completeness. (2). Replay value of the second cycle after the action with an average of 90.78 and 89.47% classical completeness. Thus, from the results of the action, it can be seen that the learning outcomes after students apply the Problem Based Learning model increase in each cycle.